2020
DOI: 10.1111/raq.12441
|View full text |Cite
|
Sign up to set email alerts
|

Co‐culture of shrimp with commercially important plants: a review

Abstract: Shrimp farming is one of the most important worldwide developed sectors; however, this development has induced a series of negative environmental impacts. One strategy to reduce these impacts is the integration or co‐culture of shrimp farming with agriculture. The integration of shrimp farming with commercial plants has been carried out with the objective of minimizing the environmental impact through the use of biosolids and effluents enriched with nutrients, taking advantage of available resources and genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 121 publications
0
10
0
Order By: Relevance
“…The first is a realization that although the current geographical intersection of agriculture and aquaculture is Asia, this will shift and significantly expand in the future as the latter gains a firmer foothold in other parts of the world. This is already occurring [18,221,239]. Second, the heterogeneity and variability of Water, Agriculture, and Aquaculture will command more attention as the effects of climate change spread and intensify [10,[240][241][242][243].…”
Section: Perspectivesmentioning
confidence: 99%
“…The first is a realization that although the current geographical intersection of agriculture and aquaculture is Asia, this will shift and significantly expand in the future as the latter gains a firmer foothold in other parts of the world. This is already occurring [18,221,239]. Second, the heterogeneity and variability of Water, Agriculture, and Aquaculture will command more attention as the effects of climate change spread and intensify [10,[240][241][242][243].…”
Section: Perspectivesmentioning
confidence: 99%
“…Under RAS conditions, the biofloc production can be achieved in bioreactors in order to use them as feeds that will promote a healthy intestinal microbiome (Kuhn et al, 2016). In another approach Mangott et al (2020) observed that the addition of Ulva lactuca macroalgae as feed for shrimp and as a bioremediation agent inside a recirculating aquaculture system (RAS) promoted the establishment of potentially beneficial bacteria in the water and in the shrimp hepatopancreas, which is reflected in the productivity variables (growth) as well as in the counts of potential pathogens.…”
Section: How the Holobiome Of The Aquaculture System Concept Is Relat...mentioning
confidence: 99%
“…Moreover, shrimp farming produces a 102 constant discharge of effluents with high concentrations of organic matter and nutrients that deteriorate the water quality of aquatic ecosystems, in which these effluents are discarded (Páez-Osuna 2001). Therefore, the integration of shrimp farming with agriculture through the irrigation of plants with these effluents could be a sustainable option for food production, as well as for the mitigation of environmental negative effects of both shrimp farming and traditional agriculture (Fierro-Sañudo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, aquaponics involves plant cultivation without soil by using only water and dissolved nutrients, which have many advantages including faster plant growth, high productivity, easy handling, and greater efficiency in water use. However, there are also disadvantages in terms of the crops, such as adverse effects due to salinity, and an excess or deficiency of nutrients (Fierro-Sañudo et al 2020). Low-salinity effluents (1 -10 g L -1 ) from shrimp farming have available nutrients (Fierro-Sañudo et al, 2020), which make them viable to grow plants, such as lettuce in salinities <2 g L -1 (León-Cañedo et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation